2017
DOI: 10.20471/acc.2017.56.01.08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitroeffects of Selenium on Human Glioblastoma Multiforme Cell Lines: A Preliminary Study

Abstract: SUMMARY -Glioblastoma multiforme (GBM) is caused by the central nervous system-derived glial cells, and represents the most common (50%-60%) form of primary brain tumors. Th e aim of this study was to investigate the in vitro eff ects of selenium on human GBM cells. In the present study, GMS-10 and DBTRG-05MG human GBM cell lines were used as a model to examine selenium entering the cell, cell proliferation, cytotoxicity, DNA fragmentation and Ki-67 protein expression in selenomethionine treated and non-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The potential influence of CD44 on tumor growth and expansion could be exerted in many ways. CD44 probably stimulates proliferation, motility and/or invasiveness of tumor cells (it probably recruites and activates matrix metalloproteinases attached to cell surface) 1,2,18 . It is also possible that CD44 promotes tumor angiogenesis by regulating endothelial cells and/or recruiting, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The potential influence of CD44 on tumor growth and expansion could be exerted in many ways. CD44 probably stimulates proliferation, motility and/or invasiveness of tumor cells (it probably recruites and activates matrix metalloproteinases attached to cell surface) 1,2,18 . It is also possible that CD44 promotes tumor angiogenesis by regulating endothelial cells and/or recruiting, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Naziroglu's group reported that Se-species stimulate glioblastoma cell death by increasing the mitochondrial ROS generation and the intracellular free calcium concentration through enhanced TRPM2 activation (Ertilav et al, 2019). Nonetheless, protective effects were observed in non-malignant cells such as neurons or microglia cells (Ataizi et al, 2019;Ertilav et al, 2019;Akyuva et al, 2021), suggesting a cellular specificity and higher affinity of Se-species on apoptosis and oxidative stress to glioma cells (Yakubov et al, 2014;Hazane-Puch et al, 2016;Harmanci et al, 2017;Yakubov, 2019). It has been previously reported that low doses of organic and inorganic forms of Se-species have antioxidant properties in malignant cell lines, but there are apoptotic effects with high dose applications (Uguz et al, 2009;Harmanci et al, 2017).…”
Section: Selenium Effects In Glioblastoma Cellsmentioning
confidence: 99%
“…In the course of the studies, it was found that methylselenol metabolites exhibit multiple beneficial chemopreventive as well as anticancer effects, whereas an excess of hydrogen selenide metabolites in a cell may cause singlestrand DNA breaks (SSBs) [7]. For this reason, it is thought that organic Se compounds are less toxic than inorganic forms that contain Se [6,9]. The anticancer mechanism of Se-containing compounds is mainly based on inducing apoptosis in cells [10], but apart from that, these compounds also affect gene expression and various cell signal pathways, DNA repair/damage, as well as the angiogenesis process or metastasis [11].…”
Section: Introductionmentioning
confidence: 99%